Novel melasma therapy using combined low fluence and microsecond pulse Q switched 1064 nm neodymium doped yttrium aluminium garnet laser - Xianglei Wu; Qingqing Cen; Xiaoxi Lin; Ying Shang; Xue Wang; Zhen Zhang (Scientific Reports)
Abstract Low-fluence Q-switched (LFQS) 1064-nm Nd: YAG laser treatment has become a standard approach for managing melasma. This study aimed to evaluate the efficacy and safety of a dual-mode approach—LFQS combined with microsecond pulse width (MPW) mode—for treating melasma. In this prospective, single-center, evaluator-blinded, split-face clinical trial, 28 patients with melasma were enrolled. One half of each face was treated using LFQS alone, whereas the other half received LFQS + MPW. Follow-ups were conducted at 1, 3, 6, and 12 months post-treatment. Of the 28 patients, 21 completed all treatments and follow-ups (5–10 sessions in total). Compared with baseline, the average Melasma Area and Severity Index score significantly decreased at 1 and 3 months. However, no significant change was observed at 6 and 12 months. The melanin index (MI) decreased significantly on both sides at 1 and 6 months, with the treatment side maintaining a significantly lower MI at 12 months. Although MI increased at 6 and 12 months, the increase was significantly less on the treatment side compared with the control side. VISIA analysis showed a significant bilateral reduction in facial pigmentation index at 1, 6, and 12 months, although the difference between sides was not statistically significant. However, the treatment side showed a significantly greater reduction in red area index at 1 and 6 months. No treatment-related adverse events were reported. The combination of low-fluence and MPW modes of Q-switched 1064-nm Nd: YAG laser is a safe and effective treatment for melasma. This dual-mode approach may help reduce relapse rates within 3 months after treatment discontinuation.